Microtubule-Directed Therapeutic Strategy for Neurodegenerative Disorders: Starting From the Basis and Looking on the Emergences - Cappelletti, Graziella; Cartelli, Daniele; S. Christodoulou, Michael; Passarella, Daniele (Current Pharmaceutical Design, 2017)
Around ten years ago, the first evidence that targeting microtubule system could be a potential strategy in slowing down neurodegeneration was reported. Several teams have been working to better shape this idea and the scientific community has now the opportunity of fishing into a large amount of data coming from in vitro and in in vivo studies. Notably, these results have driven clinical trials addressing tauopathies. Unfortunately, moving such a neuroprotective strategy from mice to men has revealed unexpected concerns and results that do not fit with the promising background. Here we aim to focus the rationale for the design of a microtubule-based therapy in neurodegeneration, look at the results achieved and discuss the future perspectives.
Keywords: therapy